Phytochemicals from Passiflora coriacea Juss. Have Anti-Inflammatory and Neuroprotective Effects in Mouse Models - Samir Castolo-Sanchez; Alejandro Zamilpa; Maribel Herrera-Ruiz; José Luis Trejo-Espino; Blanca Eda Domínguez-Mendoza; Manasés González-Cortazar; Gabriela Trejo-Tapia (MDPI AG, 2024)
Background: Neuroinflammatory diseases trigger an inflammatory response and a state of oxidative stress. Passiflora coriacea Juss. has been used to treat conditions related to inflammatory processes in the central nervous system; however, to date, there has been no study on the anti-inflammatory and neuroprotective effects of this species. Methods: The anti-inflammatory effect of P. coriacea was evaluated in a TPA-induced auricular edema model, and the percentage of edema inhibition (Ei) was recorded. The Morris water maze was used to assess the neuroprotective effect, measuring the latency time (LT), and lipopolysaccharide was administered to induce neuroinflammation. The concentrations of cytokines (IL-6, IL-10, and TNF-α) and activities of antioxidant system components (CAT, SOD, GR, NO, and MDA) were measured in the mouse brains. The chemical composition was determined using chromatographic and nuclear magnetic resonance techniques. Results: T1.1, T2.1, and T3.1 showed anti-inflammatory (Ei = 92.5, 88.3, and 64.8%, respectively) and neuroprotective (LT = 27.2, 22.9, and 27.7 s, respectively) effects. T1.1 was identified as scopolin with immunomodulatory (IL-6 = 3307 pg/g) and antioxidant (CAT = 1198 mmol, SOD = 23%, GR = 5.34 units/mL, NO = 11.5 µM, MDA = 1526 nmol/mL) effects; T2.1 was a mixture of terpenes (fitone, 7-dehydrodiosgenin, tremulone) with immunomodulatory (TNF-α = 857 pg/g) and antioxidant (CAT = 1245 mmol, NO = 8.75 µM) effects; and T3.1 was a mixture of isoquercetin and astragalin with immunomodulatory (IL-6 = 3135 pg/g, IL-10 = 1300 pg/g, TNF-α = 751 pg/g) and antioxidant (SOD = 1204 nmol/mL, CAT = 1131 nmol/mL, NO = 6.37 µM, MDA = 1204 nmol/mL) effects. Conclusions: The administration of P. coriacea treatments generated anti-inflammatory, neuroprotective, immunomodulatory, and antioxidant effects. These effects are attributable to its chemical composition, comprising scopolin, terpenes, and a mixture of isoquercetin and astragalin, which have not previously been described in this species.